2007
DOI: 10.1016/j.scriptamat.2007.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Shear bands at the fatigue crack tip of nanocrystalline nickel

Abstract: Fatigue crack growth rates in electrodeposited nanocrystalline Ni and its coarse counterpart were experimentally investigated in this paper. The shear bands, called the epsilon plastic zone, were observed on the surface of nanocrystalline Ni samples. The length of the shear bands is close to the estimated size of the plastic zone at the crack tip. Atomic force microscopy measurements indicate that the shear strain in the shear bands and the width of shear bands increase with related crack length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The presence of shear lips and dimpled rupture in those studies are also indicative of substantial ductility. Shear banding in the crack tip plastic zone has also been reported in one study of electrodeposited NC Ni [71].…”
Section: Experimental Datasupporting
confidence: 62%
See 3 more Smart Citations
“…The presence of shear lips and dimpled rupture in those studies are also indicative of substantial ductility. Shear banding in the crack tip plastic zone has also been reported in one study of electrodeposited NC Ni [71].…”
Section: Experimental Datasupporting
confidence: 62%
“…Other experimental studies using NC Ni have demonstrated the presence of dual shear bands along either side of the crack path, correlating with each loading cycle of the sample [71]. While the length of the shear bands was limited by the monotonic plastic zone size, which was several tens-of-microns under those loading conditions, the spacing between bands correlated with the spacing between striations on the fracture surfaces.…”
Section: Propagation Mechanismsmentioning
confidence: 81%
See 2 more Smart Citations
“…Thus, it is suggested that the GB mobility is improved dramatically [15,16] to mediate cyclic plastic deformation. Cyclic plastic strain accumulation will concentrate on GB-involved deformation, such as shear banding [17], GB sliding and grain rotation [18], as a dominant mechanism that would take over the conventional PSB-based fatigue mechanism [7]. Our finding of l min sp clearly indicates that cyclic strain localization through extrusions or slip lines is completely hindered when the length scale of the film is less than l min sp , and the corresponding physical mechanism of fatigue damage has been changed…”
Section: Resultsmentioning
confidence: 75%